Indoctrinating the Youth Secondary Education in Wartime China and Postwar Taiwan, 1937-1960 - Liu, Jennifer (University of Hawaii Press, 2024)
Indoctrinating the Youth examines how the Guomindang (GMD or Nationalists) sought to maintain control of middle-school students and cultivate their political loyalty over the trajectory of the Second Sino-Japanese War, Chinese Civil War, and postwar Taiwan. During the Sino-Japanese War the Nationalists managed middle-school refugee students by merging schools, publishing and distributing updated textbooks, and assisting students as they migrated to the interior with their principals and teachers. In Taiwan, the China Youth Corps (CYC) became a symbol of the regime's successful establishment. Tracing Nationalist efforts to indoctrinate ideology and martial spirit, Jennifer Liu investigates how GMD leaders Chiang Kai-shek and his son Chiang Ching-kuo tried to build support among young people in their efforts to stabilize Taiwanese society under their rule.